Model of persistent foot‐and‐mouth disease virus infection in multilayered cells derived from bovine dorsal soft palate. Issue 1 (29th August 2019) - Hägglund, Sara; Laloy, Eve; Näslund, Katarina; Pfaff, Florian; Eschbaumer, Michael; Romey, Aurore; Relmy, Anthony; Rikberg, Annika; Svensson, Anna; Huet, Helene; Gorna, Kamila; Zühlke, Daniela; et al.
Abstract: Foot‐and‐mouth disease virus (FMDV) causes a highly contagious vesicular disease in livestock, with serious consequences for international trade. The virus persists in the nasopharynx of cattle and this slows down the process to obtain an FMDV‐free status after an outbreak. To study biological mechanisms, or to identify molecules that can be targeted to diagnose or interfere with persistence, we developed a model of persistent FMDV infection in bovine dorsal soft palate (DSP). Primary DSP cells were isolated after commercial slaughter and were cultured in multilayers at the air‐liquid interface. After 5 weeks of culture without further passage, the cells were infected with FMDV strain O/FRA/1/2001. Approximately, 20% of cells still had a polygonal morphology and displayed tight junctions as in stratified squamous epithelia. Subsets of cells expressed cytokeratin and most or all cells expressed vimentin. In contrast to monolayers in medium, multilayers in air demonstrated only a limited cytopathic effect. Integrin αV β6 expression was observed in mono‐ but not in multilayers. FMDV antigen, FMDV RNA and live virus were detected from day 1 to 28, with peaks at day 1 and 2. The proportion of infected cells was highest at 24 hr (3% and 36% of cells at an MOI of 0.01 and 1, respectively). At day 28 after infection, at a time when animals that still harbour FMDV are considered carriers, FMDV antigen was detected in 0.2%–2.1% of cells, in all layers, and live virus was isolated from supernatants of 6/8 cultures. On the consensus level, the viral genome did not change within the first 24 hr after infection. Only a few minor single nucleotide variants were detected, giving no indication of the presence of a viral quasispecies. The air‐liquid interface model of DSP brings new possibilities to investigate FMDV persistence in a controlled manner.